Smoking among university students: A gender analysis - Ahmed Mandil; Abdulaziz BinSaeed; Shaffi Ahmad; Rufaidah Al-Dabbagh; Muslim Alsaadi; Mahwish Khan (Elsevier, 2010)
The main objectives of this paper were to estimate the consumption patterns of tobacco use among King Saud University (KSU) undergraduate students; and investigate different risk factors which may contribute to tobacco use among female students.A representative sample (n = 7550) of the total KSU undergraduate student population of 69,498 (males and females) was selected, stratified according to college and gender. A modified version of the WHO/CDC Global Youth Tobacco Survey (GYTS) questionnaire was used for data collection.Overall smoking prevalence among KSU students was estimated at 14.5%, prevalence among male students (32.7%), and females (5.9%). Independent risk factors for smoking among males were found to be: age, father's smoking habits, and "friends' smoking habits"; while among females were: sister's smoking habits and "friends' smoking habits."The findings of this study re-emphasize the significance of peer pressure on smoking among university students of both sexes; influence of family members, usually of same sex. We need to foster gender-sensitive tobacco prevention intervention programs, to prevent youngsters of both sexes from taking up such habit. We also need to raise awareness of girls and young women, of the consequences of smoking in general, water-pipe in specific, on their own health, that of their spouses, families, and off-springs, many of whom could develop chronic respiratory disorders, as passive smokers in the beginning/potential smokers themselves, later on. All such efforts should be backed and supported by strong governmental commitment, to ensure success of their implementation accordingly. Keywords: Smoking, Undergraduate university students, Riyadh, Saudi Arabia